Effect of chitosan and cationic starch on the surface chemistry properties of bagasse paper - Ashori, Alireza (2021)
The use of non-wood fibers in the paper industry has been an economical and environmental necessity. The application of dry-strength agents has been a successful method to enhance the strength properties of paper. The experimental results evidencing the potential of chitosan and cationic starch utilization in bagasse paper subjected to hot water pre-extraction has been presented in this paper. The research analyzes the surface properties alterations due to these dry-strength agents. Inverse gas chromatography was used to evaluate the properties of surface chemistry of the papers namely the surface energy, active sites, surface area as well as the acidic/basic character. The results of the study revealed that the handsheets process causes surface arrangement and orientation of chemical groups, which induce a more hydrophobic and basic surface. The acid-base surface characteristics after the addition of dry-strength agents were the same as the bagasse handsheets with and without hot water pre-extraction. The results showed that the dry-strength agent acts as a protecting film or glaze on the surfaces of bagasse paper handsheets.